Pola POLA ALAM SEBAGAI STRATEGI PEMBINAAN KEAGAMAAN MUALLAF MENTAWAI - alrasi, fitri (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
This study aims to find relevant educational patterns to build religious education for converts. The focus of this study is on four things: First, the religious knowledge and experience of the converts. Second, the challenges faced by converts to increase knowledge and religious experience of converts. Third, the development of religious education that can improve the religious quality of converts. Fourth, the pattern of religious education for converts. The research model used is participatory using Community Based Research (CBR) as an approach. The stages of this research include: 1) Laying the basic principles (research design), 2) Planning, 3) Data collection and analysis, and 4) Actions and findings. 5) evaluation of the results, processes and effects of the development of findings. Data collection techniques are 1) Observation, 2) Interview, 3) Questionnaire, 4) Focus Group Discussion (FGD), 5) Documentation. There are two data analysis used: First, qualitative data analysis of observation data, FGD and interviews. Second, analysis of quantitative data for the use of questionnaires on a percentage basis. This study found patterns of religious education for converts natural patterns. The results of the study above show that a participatory approach to religious education based on nature is the right solution for converts